2018
DOI: 10.4103/aja.aja_15_17
|View full text |Cite
|
Sign up to set email alerts
|

The role of peroxisome proliferator-activated receptor gamma in prostate cancer

Abstract: Despite great progress in the detection and treatment of prostate cancer, this disease remains an incredible health and economic burden. Although androgen receptor (AR) signaling plays a key role in the development and progression of prostate cancer, aberrations in other molecular pathways also contribute to the disease, making it essential to identify and develop drugs against novel targets, both for the prevention and treatment of prostate cancer. One promising target is the peroxisome proliferator-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 68 publications
0
15
0
1
Order By: Relevance
“…PPARα and PPARβ/δ expressions are detected among normal prostate, BPH, and prostate cancer tissues, while expression of PPARγ was observed in prostate cancer but not in normal prostate and BPH [34]. Furthermore, PPARγ expression was shown to increase with cancer grade/stage and correlate with poor survival in prostate cancer patients, suggesting that PPARγ plays an oncogenic role in prostate cancer development and progression [35,36,37]. Functionally, the effect on AR signaling by PPARγ is controversial and dependent on the cellular context [38].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARα and PPARβ/δ expressions are detected among normal prostate, BPH, and prostate cancer tissues, while expression of PPARγ was observed in prostate cancer but not in normal prostate and BPH [34]. Furthermore, PPARγ expression was shown to increase with cancer grade/stage and correlate with poor survival in prostate cancer patients, suggesting that PPARγ plays an oncogenic role in prostate cancer development and progression [35,36,37]. Functionally, the effect on AR signaling by PPARγ is controversial and dependent on the cellular context [38].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
“…PPARγ was originally thought to exert antioncogenic properties in prostate cancer because PPARγ agonists inhibited the growth of prostate cancer cells. However, additional studies found that PPARγ agonists inhibited cell growth independent of PPARγ [37], and fatty acids promoted tumorigenesis [39]. Indeed, recent studies showed that PPARγ activation promoted prostate cancer progression [40,41], suggesting that PPARγ inhibition might be useful in prevention and treatment for prostate cancer [42].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
“…S3), we hypothesized that FABP5 promotes metastasis by regulating lipid signaling. Previous work has established that the nuclear receptor PPARγ mediates the pro-metastatic effects of FABP5 in vitro 8,23,30 . Thus, we assessed whether FASN and MAGL enhance the metastatic potential of PCa cells via PPARγ activation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, we pursued studies with PPARγ and demonstrated that enhancement of PPARγ receptor signaling by ABA treatment promotes PCa cellular dormancy with G 0 cell cycle arrest in vitro culture conditions and in vivo animal model. Moreover, PPARγ has a role as a tumor suppressor in several types of cancer cells including PCa [42 , [50] , [51] , [52] , [53] , [54] , [55] ]. As such, what role LANCL2 ultimately plays in DTC biology of DTCs will require further studies, but clearly PPARγ appears to play the predominant role in response to ABA in PCa cells.…”
Section: Discussionmentioning
confidence: 99%